Fully automated 3D aortic segmentation of 4D flow MRI for hemodynamic analysis using deep learning - Berhane, Haben; Scott, Michael; Elbaz, Mohammed; Jarvis, Kelly; McCarthy, Patrick; Carr, James; Malaisrie, Chris; Avery, Ryan; Barker, Alex J.; Robinson, Joshua D.; Rigsby, Cynthia K.; Markl, Michael (Magnetic resonance in medicine, 2020)
Purpose To generate fully automated and fast 4D‐flow MRI‐based 3D segmentations of the aorta using deep learning for reproducible quantification of aortic flow, peak velocity, and dimensions. Methods A total of 1018 subjects with aortic 4D‐flow MRI (528 with bicuspid aortic valve, 376 with tricuspid aortic valve and aortic dilation, 114 healthy controls) comprised the data set. A convolutional neural network was trained to generate 3D aortic segmentations from 4D‐flow data. Manual segmentations served as the ground truth (N = 499 training, N = 101 validation, N = 418 testing). Dice scores, Hausdorff distance, and average symmetrical surface distance were calculated to assess performance. Aortic flow, peak velocity, and lumen dimensions were quantified at the ascending, arch, and descending aorta and compared using Bland‐Altman analysis. Interobserver variability of manual analysis was assessed on a subset of 40. Results Convolutional neural network segmentation required 0.438 ± 0.355 seconds versus 630 ± 254 seconds for manual analysis and demonstrated excellent performance with a median Dice score of 0.951 (0.930‐0.966), Hausdorff distance of 2.80 (2.13‐4.35), and average symmetrical surface distance of 0.176 (0.119‐0.290). Excellent agreement was found for flow, peak velocity, and dimensions with low bias and limits of agreement less than 10% difference versus manual analysis. For aortic volume, limits of agreement were moderate within 16.3%. Interobserver variability (median Dice score: 0.950; Hausdorff distance: 2.45; and average symmetrical surface distance: 0.145) and convolutional neural network–based analysis (median Dice score: 0.953‐0.959; Hausdorff distance: 2.24‐2.91; and average symmetrical surface distance: 0.145‐1.98 to observers) demonstrated similar reproducibility. Conclusions Deep learning enabled fast and automated 3D aortic segmentation from 4D‐flow MRI, demonstrating its potential for efficient clinical workflows. Future studies should investigate its utility for other vasculature and multivendor applications.